Strawberry Proteome Responses to Controlled Hot and Cold Stress Partly Mimic Post-harvest Storage Temperature Effects on Fruit Quality - Lv, Jinhua; Zheng, Ting; Song, Zenglu; Pervaiz, Tariq; Dong, Tianyu; Zhang, Yanyi; Jia, Haifeng; Fang, Jinggui (Frontiers in Nutrition, 2022)
To determine the effect of different temperature on strawberry after harvest, physiological indicator analysis and proteomics analysis were conducted on ripened strawberry (‘Sweet Charlie’) fruit stored at 4 °C, 23 °C, and 37 °C for 10 or 20 days. Results showed that 4 °C maintained a better visual quality of strawberry, and the weight loss and firmness remained stable within 3 days. Low temperature negatively affected anthocyanin but positively affected soluble sugars. Though anthocyanin content was higher with increasing temperature, anthocyanin synthesis related proteins were downregulated. Higher indole-acetic acid (IAA) content in seeds and lower abscisic acid (ABA) content were found in berry at 4 °C. Antioxidant related proteins were upregulated during storage, showing a significant up-regulation of peroxidase (POD) at 4 °C, and ascorbate-glutathione (AsA-GSH) cycle related proteins and heat shock proteins (HSPs) at 37 °C. In addition, overexpressed sugar phosphate/phosphate translocator, 1-aminocyclopropane-1-carboxylate oxidase and aquaporin PIP2-2 had a positive effect in response to low temperature stress for containing higher protopectin content and POD activity.